The influence of oxygen content on the Tc of HTS Hg-1245 - Itskevich, E. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
We have observed an extraordinary behavior of the HgBa2Ca4Cu5O12+d layered HTS (phase 1245) in the overdoped state. Earlier we have synthesized the phase Hg-1245 with different oxygen content and consequently different values of the lattice parameter a. We have observed a coincidence of a values when the Tc(a) cupolas reach their maxima for phases Hg-1223, 1234, and 1245, and a merging of their overdoped parts together with abrupt falling off of the Tc values. The Hg-1245 phase has shown the most unusual behavior. Contrary to other phases, this one contains three types of CuO2 layers in a unit cell. We supposed that, in the case of the Hg-1245 phase, the holes coming from the reservoir, which is the Hg-O plane, cannot reach the &quotfar&quot CuO2 layer which is notable for this phase. We have calculated the hole concentration for each layer for 1223, 1234, and 1245 phases. The results obtained confirm our assumption. The hole concentration appears negligibly small for the overdoped 1245 phase. We can consider the &quotfar&quot CuO2 layer as not taking part in superconductivity. The analysis of the behavior of the Tc(a) cupolas for the phases with different number of CuO2 layers and of hole density distribution between the layers has been carried out.